Celebrating queer lesbian desires with Dorothy Allison: From moral monstrosity to the beautiful materiality of the body - Mélanie Grué (2015)
Using social and queer theory on domination, sexuality and gender, this contribution explores how the queer American author Dorothy Allison celebrates the vilified transgressive lesbian body. As, in the 1970s, the mainstream american feminist movement crystallized around the definition of an acceptable sexuality in the name of femininity, female sexual practices were standardized according to strict identity frames, carnal desire was denied, and transgressive lesbians who play with gender roles were defined as abject. In response to this extreme taming of the body, Allison interrogates the notions of masculinity and femininity, domination and submission in her exploration of sexual pleasure and traumatized sexuality. She celebrates the aggressiveness and masculinity of queer lesbianism, promotes the fluidity of gender roles, and asserts the primacy of the flesh,sensuality, and materiality in sexuality.
Keywords: approches et analyses; arts; corps; corps lesbien; discipline; identités LGBTQIA2+; littérature; personnes lesbiennes; queer; ressource en ligne; sexualité; thématiques; études littéraires

Nina Bouraoui, martyr(s) de l’écho : de la blessure à une nouvelle sexualité par l’affect - Montalbano, Sylvain (Études littéraires, 2015)
Analysant les romans de Nina Bouraoui, en particulier Mes mauvaises pensées, Appelez-moi par mon prénom et Nos baisers sont des adieux, cet article démontre comment l’écrivaine transforme l’extrême violence de sa prose – à raconter son sentiment de blessure face aux identités distinctes d’auteure française, algérienne et queer qu’on veut lui imposer – en un véhicule capable de transmettre des affects plutôt qu’une logique narrative. En reliant certaines œuvres d’art (y compris ses propres textes littéraires) à d’autres corps dans une même virtualité en tant qu’« émetteurs-récepteurs » d’affects, Bouraoui en arrive à suggérer la possibilité d’une nouvelle sexualité queer affective, c’est-à-dire relationnelle et allant au-delà de l’orientation sexuelle de chacun(e).
Keywords: 1900-1999; approches et analyses; arts; corps; discipline; littérature; nouvelle sexualité; périodes historiques; queer; ressource en ligne; sexualité; thématiques; émotions; études littéraires